Development and Acoustic Analysis of a Speaker-Output Stethoscope for Low-Cost Clinical Applications - Wibowo, Kusnanto Mukti; Latif, Abdul; Susanto, Fani; Fatiatun, Fatiatun; Che Ani, Norhidayah (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2025)
This study addresses the limitations of traditional stethoscopes, which are constrained by their single-user design, dependence on auditory acuity, and susceptibility to background noise. These limitations hinder collaborative learning and diagnostic accuracy, particularly in noisy environments or during infectious disease outbreaks. The aim of this work is to develop a low-cost, speaker-output digital stethoscope that enables multiple users to simultaneously listen to heart sounds, improving both clinical training and infection control. The main contribution of this study is the integration of a conventional analog stethoscope with a high-sensitivity microphone preamplifier, an external speaker, and digital signal processing (DSP) algorithms. This configuration allows the amplification and filtering of heart sounds, enabling group auscultation without the need for earpieces. The device casing is constructed from High-Pressure Laminate (HPL) sheets and multiplex wood panels, while acoustic foam is used to reduce noise interference.  Heart sounds are captured via a microphone, amplified, and processed using Fast Fourier Transform (FFT) and band-pass filtering (20–150 Hz) to isolate the key frequencies. The system was tested in a quiet clinical setting, and the resulting audio was analyzed for clarity and frequency spectrum. The prototype successfully captured heart sounds, with a dominant spectral peak around 97 Hz, consistent with the primary frequency of heartbeats. It also clearly identified the first (S1) and second (S2) heart sounds. However, ambient noise affected sound clarity, indicating the need for further noise reduction. Despite this limitation, the device successfully enabled group auscultation. In conclusion, the speaker-output stethoscope offers an affordable and effective alternative to traditional auscultation, enhancing medical training and improving infection control. Although noise reduction requires further refinement, the system demonstrates strong potential for application in clinical and educational settings, particularly in low-resource environments